Beyond skills: Proactive career behaviour, positive traits and internship experience in shaping employability among Malaysian TVET graduates - Saibon, Ramdzan Ali; Zakariya, Zainizam; Zulkifli, Normala; Kamis, Arasinah; Ismail, Mohamad Amiruddin; Saibon, Jamal Safri; Zulkafli, Syamsol Azhar (Journal of Islamic, Social, Economics and Development, 2025)
Graduate employability remains a central concern within Technical and Vocational Education and Training (TVET), particularly in emerging economies facing persistent skills mismatch and labour market volatility. While skills development has long been prioritised in vocational education, growing evidence suggests that employability outcomes are increasingly shaped by behavioural and psychological factors. This study examines the effects of skills, proactive career behaviour and positive personal traits on graduate employability among Malaysian vocational college business management graduates, with internship training experience tested as a moderating variable. Using a quantitative cross-sectional design, survey data were collected from diploma graduates of Malaysian vocational colleges and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Skills were modelled as a multidimensional construct encompassing academic, technical, employability and entrepreneurial skills. Proactive career behaviour and positive traits were specified as behavioural and psychological predictors, respectively, while internship training experience was treated as a continuous moderator. The findings reveal that proactive career behaviour and positive traits significantly predict graduate employability, with positive traits emerging as the strongest determinant. In contrast, skills did not exhibit a significant direct effect, indicating that technical and academic competencies may function as baseline requirements rather than competitive differentiators in contemporary labour markets. Furthermore, internship training experience did not moderate the relationships between individual attributes and employability, although it demonstrated a significant direct effect. These results challenge skill-centric interpretations of Human Capital Theory and support more holistic employability frameworks that integrate behavioural and psychological dimensions. The study offers important implications for TVET institutions and policymakers by emphasising the need to embed career self-management competencies, positive psychological development and quality-assured internship structures within vocational education systems.